An Examination of English Instruction in a Classroom That Includes Students with Diverse Needs: A Detailed Analysis - Hamidah, Nur; Masuwd, Mowafg Abrahem (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
The study focused on examining the instructional methods employed by English teachers in inclusive classrooms, as well as the typical difficulties encountered by these teachers in teaching in such settings. The researchers employed qualitative research methodology utilizing the case study approach, employing two primary instruments, namely interviews and observations. The research involved a school coordinator responsible for inclusive education, an English teacher who taught in inclusive classrooms, and children with special needs. The data were gathered over two weeks through two interviews and two outdoor observations. The data acquired were recorded using several methods, including tape recording, field notes, photos, and videos. The data were subjected to qualitative analysis to address the research topics. The study's findings are classified into three primary categories. The school provides programs that promote the implementation of inclusive education, including self-development programs and additional courses that help the development of basic life skills for students with special educational needs (SEN). There are 10 classes designated to accommodate at least one student with special needs in each session. Furthermore, in instructing English in inclusive classrooms, the teachers demonstrated a deficiency in employing targeted methodologies. However, they did utilize game-based technology such as Kahoot to facilitate engaging and pleasurable learning experiences. Furthermore, the outcome also indicates that the qualities of patience and sincerity hold significant importance in instructing students with special educational needs (SEN).